More of the same: new policies continue fostering the use of non-native fish in Brazil - Garcia, Diego AZ; Occhi, Thiago VT; Agostinho, Ângelo A; Alves, Gustavo HZ; Brito, Marcelo FG; Casimiro, Armando CR; Couto, Thiago BA; Cunico, Almir M; Jarduli, Lucas R; Lima-Junior, Dilermando P; Magalhães, André LB; Novaes, José Luís C; et al. (Environmental conservation, 2022)
First authorized in the state of São Paulo (State Decree Nº 62.243 November 2016), striped catfish farming has been progressively allowed and encouraged in other states (Garcia et al. 2018). Fish are not constrained by geopolitical boundaries (Latini et al. 2021). [...]despite the limitations imposed by geographical barriers, the potential expansion of the striped catfish to other Brazilian states or even to other South American countries should not be underestimated. If fish farm escapes and releases by aquarists become more frequent, the chances of establishment of P. hypophthalmus will be greater. [...]the propagule pressure of P. hypophthalmus may increase, as this consists of both the number of individuals introduced by events and the frequency of events (Lockwood et al. 2009). Because the striped catfish displays traits associated with high invasiveness (see Garcia et al. 2018), it is considered a potential threat to Neotropical ecosystems and native catfishes (Castellanos-Mejía et al. 2021).